Free nitrous acid (FNA) induced transformation of sulfamethoxazole in the enriched nitrifying culture - Sun, Faqian (2020)
The sulfonamide antibiotics sulfamethoxazole (SMX) has been frequently detected in the wastewater. It has been reported that part of SMX can be transformed by the co-metabolism of ammonia oxidizing bacteria (AOB) during nitrifying process. However, previous studies reported inconsistent or even contradictory results in terms of SMX degradation and/or transformation. Literature study revealed that nitrite may play certain role in SMX transformation, which has been neglected previously. In this study, the transformation behavior of SMX was investigated with and without the presence of nitrite in an enriched nitrifying culture. The results clearly show that the elimination of SMX occurred with the presence/accumulation of nitrite, and a linear regression was observed between SMX elimination efficiency and free nitrous acid (FNA) concentration, indicating that FNA was the major factor responsible for the SMX transformation. By reacting with FNA, SMX transformation products, such as 4-nitro-SMX, desamino-SMX and hydroxylated SMX, were detected. However, when FNA concentration decreased, these intermediates may be retransformed back to SMX. These findings improved our understanding on SMX transformation in a biological system and highlighted the role of nitrite/FNA in the sulfonamide antibiotics degradation.